2011
DOI: 10.1002/esp.2267
|View full text |Cite
|
Sign up to set email alerts
|

How natural are Alpine mountain rivers? Evidence from the Italian Alps

Abstract: Historical, human‐induced channel adjustments in lowland gravel‐bed rivers have been documented in several geographical contexts worldwide. In particular, it is now widely accepted that the vast majority of European rivers are far from any natural, reference state prior to anthropic disturbances, and a ‘complete’ restoration is hardly achievable. However, few investigations have addressed changes that have occurred in mountain rivers of the Alps, and these channels are commonly reckoned quite ‘natural’ by soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 55 publications
6
98
0
2
Order By: Relevance
“…Most fluvial systems in Europe (e.g., Petts et al, 1989;Billi et al, 1997;Comiti, 2012)-as well as in other continents (e.g., Montgomery, 2008)-have been affected by humans for several centuries or even thousands of years, rendering fluvial systems the result of a long interplay between climatic, geological, and human factors. This evidence led many authors to conclude that referring to a 'pristine' stream condition is neither feasible nor worthwhile (e.g., Kern, 1992;Rhoads and Herricks, 1996;Rhoads et al, 1999;Jungwirth et al, 2002;Downs and Gregory, 2004;Kondolf and Zolezzi, 2008;Piégay et al, 2008;Dufour and Piégay, 2009;Wyżga et al, 2012).…”
Section: Reference Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most fluvial systems in Europe (e.g., Petts et al, 1989;Billi et al, 1997;Comiti, 2012)-as well as in other continents (e.g., Montgomery, 2008)-have been affected by humans for several centuries or even thousands of years, rendering fluvial systems the result of a long interplay between climatic, geological, and human factors. This evidence led many authors to conclude that referring to a 'pristine' stream condition is neither feasible nor worthwhile (e.g., Kern, 1992;Rhoads and Herricks, 1996;Rhoads et al, 1999;Jungwirth et al, 2002;Downs and Gregory, 2004;Kondolf and Zolezzi, 2008;Piégay et al, 2008;Dufour and Piégay, 2009;Wyżga et al, 2012).…”
Section: Reference Conditionsmentioning
confidence: 99%
“…In this respect, the work of Jungwirth et al (2002) is valuable because it emphasizes that assessment can be a two-step process, i.e., firstly, deviations from natural conditions ('visionary leitbild') are assessed, followed by the identification of restoration goals ('practical leitbild'). The appropriateness of identifying river 'degradation' history before reasoning about possible restoration actions has recently been argued for Alpine rivers by Comiti (2012).…”
Section: Reference Conditionsmentioning
confidence: 99%
“…A complementary ingredient for effective environmental management would be to understand the causes and controls of those evolutionary river trajectories. Broadly speaking, the decrease of active channel width has been explained by the concurrent effect of different factors, including climate change, land use change, dam construction and in-channel gravel mining [49]. The present study does not attempt to account for the causality of the observed changes on the selected Albanian rivers; for this, further research is needed.…”
Section: Discussion and Future Prospectsmentioning
confidence: 94%
“…The beginning of the 19 th century corresponds to the end of the Little Ice Age, a cold period with a high sediment transport and hydrologic activity [20]. As a distant consequence, aggradation and widening of some rivers was observed [21], and stream beds and fluvial activity areas were larger than today.…”
Section: Natural Hazard Changementioning
confidence: 99%